2013
DOI: 10.12692/ijb/3.2.87-98
|View full text |Cite
|
Sign up to set email alerts
|

Callus growth and plant regeneration in durum wheat (Triticum durum Desf.) immature embryos under abscisic acid (ABA) treatment

Abstract: The effect of abscisic acid (ABA) on callus growth and plant regeneration was studied in Four cultivars of durum wheat considered to have a good ability for in vitro culture. calluses induced from immature embryos on MS medium supplemented with 2 mg/l 2,4-dichlorophenoxyacetic acid (2,4-D) were transferred onto the same medium supplemented with different concentrations of ABA (0, 1, 2, 4 and 10 µM). The regeneration medium used was MS medium supplemented with 0.2 mg L-1 of 2,4-D, 10μM of benzylaminopurine (BAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
1
0
3
Order By: Relevance
“…Із наукових літературних джерел [4,7,9] відомо, що морфогенез in vitro характеризується багатьма аспектами, зокрема такими, як фітогормональне сприйняття, дедиференціація диференційованих клітин для надбання компетентності до органогенезу, повернення спочиваючих клітин до клітинного циклу й організація поділу клітин для формування примордіїв певних органів і меристем. Тотипотентність культивованих клітин, тобто здатність перейти до виконання програми розвитку, визначається, насамперед, генотиповими особливостями, тому дослідження були розпочаті з вивчення реакції ліній пшениці на умови культивування in vitro.…”
Section: результати та обговоренняunclassified
See 2 more Smart Citations
“…Із наукових літературних джерел [4,7,9] відомо, що морфогенез in vitro характеризується багатьма аспектами, зокрема такими, як фітогормональне сприйняття, дедиференціація диференційованих клітин для надбання компетентності до органогенезу, повернення спочиваючих клітин до клітинного циклу й організація поділу клітин для формування примордіїв певних органів і меристем. Тотипотентність культивованих клітин, тобто здатність перейти до виконання програми розвитку, визначається, насамперед, генотиповими особливостями, тому дослідження були розпочаті з вивчення реакції ліній пшениці на умови культивування in vitro.…”
Section: результати та обговоренняunclassified
“…Біотехнологічні підходи прискорюють селекційний процес завдяки скороченню часу, необхідного для виведення сортів із поліпшеними характеристиками, а також доповнюють та розширюють генетичну мінливість, необхідну для отримання нових сортів із заданими ознаками [1][2][3]. Методи культури тканин in vitro різних експлантів (органів або частин органів, ізольованих від донорної рослини) нині широко використовуються для вирішення прикладних завдань селекції цінних сільськогосподарських рослин, зокрема пшениці [4][5][6].…”
unclassified
See 1 more Smart Citation
“…Previously, Christianingsih (2008) stated that the role of gibberellins in cell elongation is to induce the formation of hydrolase and proteolase enzymes to release amino acid tryptophan as an auxin precursor, thereby increasing auxin levels. An increase in auxin level and inhibition of abscisic acid (ABA) will break the embryo dormancy, so the embryo can germinate and grow (Wattimena et al, 2011;Bouiamrine et al, 2013). Research results showed that cultured 3 and 4…”
Section: Immature Embryo Germinationmentioning
confidence: 99%